MINAT REMAJA MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI DITINJAU DARI KONDISI EKONOMI KELUARGA DI DESA MANYABAR KECAMATAN PANYABUNGAN - Vitria, Dela (JUANG: Jurnal Wahana Konseling, 2019)
ABSTRACTEducation has an important role in showing national civilization. The goverment is required to concentrate to improve and advance the quality and quantity of education continuously. Therefore the authort are interested in examining the interest of adolescents in continuing their education to higher education in terms of the family economic conditions in the manyabar village of panyabungan sub-district. The aim to be achieved in this study is to determine the economic level of parents wits interest in adolescents continuing their education to college. The approach taken in this study are three teenagers who did not continue their education to college. Data collection used is observation, interviews, and documentation. The results of this study indicate that the economic cindition of the family strongly influenced adolescents in this village to continua their education to college.Keywords: Teenage , Education, College, Economic